French literary fascism : nationalism, anti-Semitism, and the ideology of culture - Carroll, David, 1944- (Princeton University Press, 1995)
This is the first book to provide a sustained critical analysis of the literary-aesthetic dimension of French fascism--the peculiarly French form of what Walter Benjamin called the fascist "aestheticizing of politics." Focusing first on three important extremist nationalist writers at the turn of the century and then on five of the most visible fascist intellectuals in France in the 1930s, David Carroll shows how both traditional and modern concepts of art figure in the elaboration of fascist ideology--and in the presentation of fascism as an art of the political. Carroll is concerned with the internal relations of fascism and literature--how literary fascists conceived of politics as a technique for fashioning a unified people and transforming the disparate elements of society into an organic, totalized work of art. He explores the logic of such aestheticizing, as well as the assumptions about art, literature, and culture at the basis of both the aesthetics and politics of French literary fascists. His book reveals how not only classical humanism but also modern aesthetics that defend the autonomy and integrity of literature became models for xenophobic forms of nationalism and extreme "cultural" forms of anti-Semitism. A cogent analysis of the ideological function of literature and culture in fascism, this work helps us see the ramifications of thinking of literature or art as the truth or essence of politics. -- Publisher description.